2022
DOI: 10.1186/s12912-022-00888-0
|View full text |Cite
|
Sign up to set email alerts
|

Nurses, physicians and patients’ knowledge and attitudes about nurse prescribing

Abstract: Background One of the roles that nurses have acquired in recent years is the role of prescribing. This study aimed to investigate the knowledge and attitudes of critical care nurses, physicians and patients about nurse prescribing. Methods A descriptive cross-sectional study with the participation of 152 nurses, 53 physicians and 75 patients was carried out. Participants were selected by stratified random sampling from the critical care units of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It will positively affect the public and medical professionals’ attitudes to some extent. In our study, doctors and medical students in the medical forum actively engaged in the discussion of nurse prescribing, which is consistent with the results of the previous studies conducted on physicians or nurses by Haririan [ 17 ], Heller [ 33 ], Zarzeka [ 37 ], Kroezen [ 38 , 61 ], and Funnell [ 44 ]. This phenomenon denoted that nurse prescribing has won medical professionals’ attention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It will positively affect the public and medical professionals’ attitudes to some extent. In our study, doctors and medical students in the medical forum actively engaged in the discussion of nurse prescribing, which is consistent with the results of the previous studies conducted on physicians or nurses by Haririan [ 17 ], Heller [ 33 ], Zarzeka [ 37 ], Kroezen [ 38 , 61 ], and Funnell [ 44 ]. This phenomenon denoted that nurse prescribing has won medical professionals’ attention.…”
Section: Discussionsupporting
confidence: 90%
“…Differences in medical policies, culture, and economic conditions in developing countries have led to limited research on nurse prescribing status and satisfaction. Only eleven developing countries’ studies have demonstrated that nurse prescribing alleviates the primary physician shortage [ 16 , 17 ]. Meanwhile, some studies have pointed out that patients are inclined to choose physicians over nurses when choosing services under the long-standing concept of prioritizing doctors over nurses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] In another study, in addition to the legal and ethical aspects of nurse prescription, training nurses on drug prescription and strengthening their clinical decision-making were other important issues that facilitated the implementation of nurse prescription. [ 6 21 ] Therefore, the government’s proper strategy and facilitating the new role of nurses in prescription medication is essential for nurses. [ 22 ] Lack of support and negative organizational atmosphere were other concepts of the challenge of nurse prescription in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the physicians advocated for critical care nurses to have the ability to prescribe medication. They emphasized that nurse prescribing enhances patient satisfaction and positively impacts the nursing profession [ 21 ]. This aligns with the results of Shannon et al‘s (2011) study, which examined the perspectives of general practitioners and specialist physicians regarding the prescribing role of heart failure specialist nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, approximately half of the respondents believed that nurse and midwife prescribing reduces the burden of responsibility on physicians [ 22 ]. Haririan et al‘s study in Iran (year not provided) revealed that the majority of specialized care physicians perceived that nurse prescribing of medications contributes to increased patient satisfaction and positively impacts the nursing profession [ 21 ]. Similarly, a study conducted in the Netherlands in 2014 demonstrated a positive outlook from both physicians and nurses regarding nurse prescribing [ 6 ].…”
Section: Discussionmentioning
confidence: 99%